2015
DOI: 10.4049/jimmunol.1400806
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Inhibits Th17 Cell Differentiation through Inhibition of RORγT Transcription by Recruiting the ERα/REA Complex to Estrogen Response Elements of the RORγT Promoter

Abstract: The symptoms of vaginal candidiasis exacerbate in the second half of the menstrual cycle in the premenopausal women when the serum estradiol level is elevated. Estradiol has been shown to inhibit Th17 differentiation and production of antifungal interleukin-17 (IL-17) cytokines. However, little is known about the mechanisms. In the present study, we used mouse splenocytes and found that estradiol inhibited Th17 differentiation through down-regulation of Rorγt mRNA and protein expression. Estradiol activated ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 58 publications
1
73
2
1
Order By: Relevance
“…It was demonstrated that p300 acetylates RORγt at K81 (increasing its activity), whereas HDAC1 reduces acetylation of RORγt (which decreases its activity, although it was not studied which lysine was involved) in HEK293T cells and isolated naive T cells from healthy human subjects [105]. In line with this, MS-275 has been reported to enhance Th17 differentiation in mouse splenocytes [106]. On the other hand, the HDACi givinostat downregulated the IL-6 receptor on T cells which reduced their ability to differentiate into Th17 cells, but instead skewed differentiation toward the Treg phenotype [107].…”
Section: Can Hdaci Alter the Balance Between Tregs And Th17 Cells?supporting
confidence: 48%
See 2 more Smart Citations
“…It was demonstrated that p300 acetylates RORγt at K81 (increasing its activity), whereas HDAC1 reduces acetylation of RORγt (which decreases its activity, although it was not studied which lysine was involved) in HEK293T cells and isolated naive T cells from healthy human subjects [105]. In line with this, MS-275 has been reported to enhance Th17 differentiation in mouse splenocytes [106]. On the other hand, the HDACi givinostat downregulated the IL-6 receptor on T cells which reduced their ability to differentiate into Th17 cells, but instead skewed differentiation toward the Treg phenotype [107].…”
Section: Can Hdaci Alter the Balance Between Tregs And Th17 Cells?supporting
confidence: 48%
“…Increased Treg suppressive function (in combination and alone) EX-527 increased acetylation of K31, K262 and K267, and increased the stability and levels of the transcription factor [91,96] Foxp3/Tregs HDAC1-3 inhibitor MS-275 Ambiguous effects [98][99][100] RORγt/Th17 HDAC1-3 inhibitor MS-275 Enhanced Th17 differentiation in mouse splenocytes [106] RORγt/Th17 Pan HDACi givinostat Downregulated the IL-6 receptor on T cells that reduced their ability to differentiate into Th17 cells, but instead skewed differentiation toward the Treg phenotype [107] Foxp3 and RORγt Pan HDACi TSA Increased Foxp3 and decreased RoRγt levels in an ovalbumin challenge asthma mouse model [38] HDAC: Histone deacetylase; HDACi: Histone deacetylase inhibitor; PBMC: Peripheral blood mononuclear cell; TSA: Trichostatin A.…”
Section: Macrophages: Selective Regulation Of the Nf-κb Transcriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 In humans, a recent paper found no effect of estradiol in the secretion of IL-17 by T cells in patients affected by multiple sclerosis, 42 whereas another suggests that estradiol inhibited Th17 differentiation through downregulation of Rorgt mRNA and protein expression. 45 Nevertheless, in these studies, the effect of estradiol was evaluated in vitro on cells from patients not in menopause and in men. Hence, the results cannot be extended to women in menopause.…”
Section: Inflammatory Diseases Immune System and Bonementioning
confidence: 99%
“…36,37 Some Candida species possess a cytosolic estrogen receptor that could mediate direct transcriptional responses to host hormones. 38 Furthermore, estrogen has been shown to disrupt neutrophil chemotaxis to the vaginal epithelium 39 and inhibit Th17 cell differentiation, 40 resulting in heightened host vulnerability to pathogens, such as Candida. Clinical and anecdotal reports frequently link symptomatic Candida vaginitis to the luteal phase, just prior to menses, which is marked by both a high estrogen state and increased vaginal pH.…”
Section: Fungal Commensalism In the Vaginamentioning
confidence: 99%